Comparison of tet (X4)-containing contigs assembled from metagenomic sequencing data with plasmid sequences of isolates from a cohort of healthy subjects - Ding, Yichen; Er, Shuan; Tan, Abel; Gounot, Jean-Sebastien; Saw, Woei-Yuh; Tan, Linda Wei Lin; Teo, Yik Ying; Nagarajan, Niranjan; Seedorf, Henning (Microbiology spectrum, 2024)
The global rise in antibiotic resistance makes it necessary to develop and apply new approaches to detect and monitor the prevalence of antibiotic resistance genes in human populations. In this regard, of particular interest are resistances against last-resort antibiotics, such as tigecycline. In this study, we show that metagenomic sequencing can help to detect high abundance of the tigecycline resistance gene tet (X4) in fecal samples from a cohort of healthy human subjects. However, cultivation-based approaches currently remain the most reliable and cost-effective method for detection of antibiotic-resistant bacteria.